Interactions between blades and abradable coatings: A numerical approach considering geometrical nonlinearity. (1st February 2021) - Xiao, Jiaguangyi; Chen, Yong; Chen, Dawei; Tian, Jie; Ouyang, Hua; Wang, Anjenq
Highlights: A numerical strategy concerns rubbing between flexible blade and abradable coating. Nonlinearity of geometry is considered in the mathematical model of blade rubs. Numerical method is verified according to experimental observations. Critical parameters that affect rub-related nonlinear behaviors are evaluated. Abstract: Blades in modern aero engines are designed to be larger and geometrically more complex; this enhances the nonlinear effects on the blade vibrations caused by blade-coating interactions arising from the tighter blade-casing clearance. This paper proposes a numerical strategy to capture the interacting behaviors between blades and abradable coatings. The geometrical nonlinearities of the blades are considered in the numerical strategy. The blades are modeled using co-rotational finite elements based on the Euler-Bernoulli beam theory. The abradable coatings are modeled using rod elements, and the casing surfaces are smoothed using b-spline surfaces. Incremental iterative processes based on the Newton-Raphson method are employed to solve the nonlinear dynamic equations and determine the contact configurations. Experimental observations are utilized to assess and verify the numerical method. Based on the proposed method, critical parameters that affect the nonlinear behaviors of blade-casing interactions are identified. The numerical process and results can form the basis for further rubbing analysis in which the geometrical nonlinearities of blade models are considered. Graphical abstract: Image, graphical abstract